(3GdSdhc GdJfXjej aj efXeGJ GdCYeGds - (3Thbj fGLj(B, (3LhGOs ((3YeGf(B:s (3OGQ GdMGeO ddfTQ hGdJhRjY(B,s, 2010)
(3GdSdhc GdJfXjej h GdSdhc GdGfSGfj, GdOGaYjI h GdJQZjH ddYed , GdJYde h GdJKbja, CfTWI CNQi PGJ GfYcGSGJ SdhcjI dOi GdGaQGO, GdJYGed eY GdGNQjf, GdKbGaI, GdJMhd eONd JZjjQ GdaQO h JWhQg, ehVhYGJ Yf WHjYI GdHTQjIs
Keywords: (3EOGQI GdCYeGds; (3GdSdhc GdEOGQjs; (3JfXje hEOGQIs